The problems of protecting the rights of heirs of intellectual rights in court (Халықаралық қатынастар және халықаралық құқық сериясы, 2020)
This article is devoted to the analysis of problems arising in the process of judicial protection ofintellectual property rights of heirs. The article, on the basis of doctrinal and legal sources, confirms theabsence of the right for the heirs of the author to demand moral compensation in case there is a limit tothe work of the author or the artisans, which is one of the practices to protect the judiciary.In addition, the authors determined that in the presence of a judicial dispute concerning the privacyrights of a particular individual, this fact could be verified. by any evidence, including an alienationagreement, and the presence of the corresponding state registration. Also, during the preparation of thisarticle, the authors have made a decision that status of the heir of exclusive rights is determined by theconceptual difference in the rights included in the estate, that is, property rights or non-property, andalso directly depends on the limits of rights and duties of the testator, which determines the methodsused judicial protection. At the same time, the study made it possible for us to realize that, despite thepresence in the Republic of Kazakhstan of a number of legislative provisions regulating the issue thescope on the rights of each holder of exclusive rights to judicial protection, it remains an urgent problem.Key words: protection, court, author, intellectual property, exclusive right.